Using a Patient Safety/Quality Improvement Model to Assess Telehealth for Psychiatry and Behavioral Health Services Among Special Populations During COVID-19 and Beyond. Issue 4 (July 2021) - Li, Luming; Childs, Amber W.
Abstract : Telehealth has been rapidly deployed in the environment of the Coronavirus 2019 (COVID-19) pandemic to help meet critical mental health needs. As systems of care use telehealth during the pandemic and evaluate the future of telehealth services beyond the crisis, a quality and safety framework may be useful in weighing important considerations for using telehealth to provide psychiatric and behavioral health services within special populations. Examining access to care, privacy, diversity, inclusivity, and sustainability of telehealth to meet behavioral and psychiatric care needs in geriatric and disadvantaged youth populations can help highlight key considerations for health care organizations in an increasingly electronic health care landscape.